2009
DOI: 10.1016/j.cpr.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in factors influencing alcohol use and drinking progression among adolescents

Abstract: While prevalence rates for alcohol use and related disorders differ widely between adult men and women, male and female adolescents do not exhibit the same disparity in alcohol consumption. Previous research and reviews do not address the emergence of differences in drinking patterns that occur during late adolescence. Therefore, a developmental perspective is presented for understanding how various risk and protective factors associated with problematic drinking affect diverging alcohol trajectories as youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
252
5
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(294 citation statements)
references
References 149 publications
(172 reference statements)
24
252
5
13
Order By: Relevance
“…These findings can be explained by the earlier puberty among girls, which makes them more prone to consuming alcohol. However, with time, they are overcome by the boys 19 . The risk of using tobacco was higher among students attending public schools, and the risk of the regular intake of alcohol and trying other drugs was higher among those attending private schools, which, in this study, would be the closest factor indicating higher socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be explained by the earlier puberty among girls, which makes them more prone to consuming alcohol. However, with time, they are overcome by the boys 19 . The risk of using tobacco was higher among students attending public schools, and the risk of the regular intake of alcohol and trying other drugs was higher among those attending private schools, which, in this study, would be the closest factor indicating higher socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Gender based studies of behaviours such as alcohol consumption [15] could be a starting point for the gender analysis of sexual relations, and this could be of use for policy makers who are increasingly concerned with offering women specific health goods and services that go beyond questions related to reproduction [16].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing salience of gender role stereotypes during adolescent development juxtaposed against socialization pressures from peers can heighten adolescents' awareness about the consequences of deviating from masculine and feminine norms for males and females, respectively. For instance, studies have shown that early adolescents perceive social status and risky, defiant behaviors to be more closely associated with male popularity and peer approval (Closson 2009;Iwamoto and Smiler 2013;Mahalik et al 2007;Rienzi et al 1996;Schulte et al 2009), and males who deviate from gender-congruent expectations experience negative social consequences, such as peer rejection (Bosson et al 2006;Mora 2012). As a result, males may feel socialization pressures to assert traditionally masculine behaviors such as rule-breaking and defiance.…”
Section: Adolescent Males' Heightened Susceptibility To Deviant Peer mentioning
confidence: 99%